PERAN DAN KEDUDUKAN MAJELIS TAKLIM DI INDONESIA - Zaini Dahlan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2019)
This article aims to examine the role and position of the Majelis Taklim as a non-formal educational institution that has religious characteristics held by the community. Majelis Taklim has a very strategic role in carrying out one of its functions to educate and provide services to the people. The strategic roles in question are the role of the Taklim Council as the ummah's educational institutions, the ummah's economic improvement institutions and the ummah's mental health institutions. To carry out this role, seeing the real conditions in Indonesia at this time, it seems that each Majelis Taklim needs to make various improvements in an effort to improve quality. These improvements can be concentrated into four fields, namely the curriculum field, the field of facilities and infrastructure, the institutional and power sector (HR). In the education legislation system, the Majelis Taklim position has a strategic place because it has a strong legal basis as a non-formal educational institution. Later, every Majelis Taklim must be registered with the Ministry in accordance with Minister of Religion Regulation No. 29 of 2019 concerning the Majelis Taklim. The reason for the implementation of this policy is to facilitate the Ministry of Religion RI in registering and providing assistance to the Majelis Taklim.